Perinatal Outcomes were Associated with the Positional Relationship between Placenta and Adenomyotic Lesion in Pregnant Patients with Adenomyosis - Ping Xu; Xiaoqing He; Yanan Zhang; Yayun Wang; Gen Zou; Jianzhang Wang; Xinmei Zhang (Clinical and Experimental Obstetrics & Gynecology)
Background: The adverse perinatal outcome caused by adenomyosis has been widely concerned recently, but little attention has been paid to whether the positional relationship between placenta and adenomyotic lesion influences the maternal and perinatal outcomes. Methods: A total of 311 women with adenomyosis who were pregnant greater than 20 weeks gestation and delivered at Women’s Hospital, Zhejiang University School of Medicine between January 2010 and December 2021 were recruited. The positional relationships between placenta and adenomyotic lesions were determined. The patients were divided into two subgroups: group 1, placenta located on or above the adenomyotic lesion; and group 2, placenta located far away from the adenomyotic lesion. The clinical data of two groups were retrospectively analyzed. Results: We found a higher rate of diffuse adenomyosis (62.65% vs. 46.21%, p = 0.01), coexisting endometriosis (31.93% vs. 15.86%, p = 0.002), preterm delivery (34.94% vs.15.17%, p < 0.001) and placenta malposition (19.88% vs. 6.90%, p = 0.002) in group I compared to group II. Compared with group II, group I had lower birth weight (p = 0.02). After adjustment using multiple logistic regression analysis, maternal adverse outcome was only correlated with age (p = 0.02). Neonatal adverse outcomes were closely correlated with group I (p = 0.004), including pregnancy induced hypertension (p = 0.01), placenta malposition (p = 0.02), placental abruption (p = 0.003), and scarred uterus (p = 0.02). Conclusions: The positional relationships between the placenta and adenomyotic lesions were graphically presented. Placental position near or above adenomyosis lesions might correlate to the adverse perinatal outcomes of pregnant women with adenomyosis and thereby deserve more attention.